Occurrence of wildfire in peat/coal forming periods and its influence on paleoclimate in the Permo-Carboniferous - Jiabao Chu; Vivek Mishra; Yanheng Li (Energy Exploration & Exploitation)
Wildfire episodes have implications on reshaping life on earth. This article emphasises on the fate and facts of wildfire during Permo-Carboniferous coal-forming period. Charcoal refers to an incomplete combustion or carbonised solid residue of plant material. Inertinite (group of coal macerals) is synonym of charcoal at microscopic scale but its origin is debatable. Moreover, inertinite has been used to predict levels of atmospheric oxygen, as it forms when plant material is subjected to intense heat and oxygen-rich conditions. In addition, soot and polycyclic aromatic hydrocarbons (PAHs) are recognized as additional evidence of palaeo-wildfires. A total number of fourteen (14) countries reported data are summarised here and the research gap has been focused particularly on the occurrences of palaeo-wildfire. These areas are also obstructed by different geological processes which are also described in detail. The several studies point out towards the global wildfire events during the Permo-Carboniferous period. These wildfires were proved by charcoals (remnants of burned plant material), inertinite macerals (microscopic components of coal) and PAHs (complex organic molecules) in the coal measures. In the same time, the large amounts of greenhouse gases have released by wildfires, and must have led to long-term changes in the atmospheric composition, which could have affected the palaeoclimate.